2021
DOI: 10.3389/fpsyt.2021.769693
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Features and Outcomes of 124 Italian Patients With Treatment Resistant Depression: A Real-World, Prospective Study

Abstract: Introduction: Treatment-resistant depression (TRD) is a debilitating condition affecting 20–30% of patients with major depressive disorders (MDD). Currently, there is no established standard of care for TRD, and wide variation in the clinical approach for disease management has been documented. Real-world data could help describe TRD clinical features, disease burden, and treatment outcome and identify a potential unmet medical need.Methods: We analyzed the Italian data from a European, prospective, multicentr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 43 publications
1
7
0
Order By: Relevance
“…Regarding the "Treatment journey and its organizational implications" (statements 4,5,6,13,16,17), the surveyed physicians agreed on the need for long-term treatment and providing TRD patients with appropriate and approved treatments. However, there was low consensus and indecision about waiting 3-4 weeks before modifying an ineffective antidepressant treatment (statement 6).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Regarding the "Treatment journey and its organizational implications" (statements 4,5,6,13,16,17), the surveyed physicians agreed on the need for long-term treatment and providing TRD patients with appropriate and approved treatments. However, there was low consensus and indecision about waiting 3-4 weeks before modifying an ineffective antidepressant treatment (statement 6).…”
Section: Discussionmentioning
confidence: 99%
“…TRD is a complex condition influenced by genetic, clinical and environmental factors, as well as comorbidities and psychosocial factors [4]. Patients with TRD experience a higher burden of illness compared to responders, including more severe symptoms, greater disability, and reduced quality of life [2,5]. The economic burden of TRD is also significant, with higher direct and indirect costs compared to nontreatment-resistant depression [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A thorough description of TRAL’s methodology can be found in previous publications of the project ( 12 , 39 ). This study followed a similar approach to other real-world studies set on characterizing the clinical and non-clinical outcomes of TRD based on the routine standard of care ( 16–18 , 33 , 40 ). The importance of real-world evidence in this context should not be understated given the differences between clinical trials and the routine management of TRD patients, in which real-world evidence better depicts the treatment unmet needs.…”
Section: Methodsmentioning
confidence: 99%
“…In this regard, the impact on instrumental activities of daily living (IADLs) should be considered, which should desirably be returned to the state previous to the episode of MDD/TRD. Previous real-word evidence has shown that outcomes of MDD/TRD are significant in dimensions such as quality of life and disability, and this is more evident in non-responders to treatment ( 16 ). The significanlty high indirect effect of absenteeism should not be discarded, as it accounts for 70% of the costs associated with a major depressive episode in a study in Belgium ( 37 ).…”
Section: Introductionmentioning
confidence: 99%